Negotiating professional boundaries: professional and organisational contingencies for pharmacist prescribing - Lafond, Natasher A. (2017)
This thesis explores boundary work, practices and changes in the pharmacy profession. Specifically it examines boundary changes that support non-medical prescribing practice for pharmacists in the context of prescribing policies and strategies which both utilise the skills of the pharmacist and also give patients greater choice and access to services.